583 Hartmann's is a safe and cost effective alternative to HAS for post operative fluid resuscitation in post cardiac surgery infants. (17th August 2022) - Ramakrishnan, Sajini; Kumar, Ramesh
Abstract : Aims: To determine safety and efficacy of changed fluid strategy in post cardiac surgery infants. Methods: This was a retrospective cohort study of infants' ≤90 days who underwent cardiac surgery in a tertiary PICU during two different 12-month time intervals when the resuscitation fluid of choice was changed. The null hypothesis was there is difference in length of stay between HAS and Hartmann's group. A total of 146 infants were included: 59 from 2016 to reflect the practice where 5%-HAS was predominant resuscitation fluid (HAS group) and 87 from 2019 when the practice of Hartman based resuscitation fluid (Hartmann's group) was firmly established. Data were collected from electronic records regarding patient demographics (age, weight), surgical parameters (RACHS, CPB, cross clamp time, delayed chest closure) and postoperative clinical parameters (acidosis/lactate on admission, day of chest closure in those who came to the unit as open chest, blood products used per kg during the first and second days and from 3rd to 7th day, resuscitation fluid received per kg during the first and second days and from 3rd to 7th day of PICU stay, inotropes on admission and during the first week, days spent in PICU, day of extubation, any AKI during the stay, co-morbidities and any other procedures undergone during the ICU stay) ( table 1 ). The primary outcome variables were length of PICU stay and day of chest closure. The groups were compared in terms of demographics, RACHS and chest open cases. Regression analysis was used to find association between the fluids/blood products and the length of stay ( figure 1 ). More number of ventilated days correlated directly to longer stays in PICU. The Hartmann group found to be having lesser days in PICU eventhough it was found to be statistically similar in each group, rejecting null hypothesis. Results: The two cohorts were comparable in baseline characteristics. They were statistically comparable in terms of RACHS category and distribution of chest open cases. There were no significant difference between the two groups in terms of length of stay in ICU, day of chest closure and prevalence of AKI. Conclusion: This retrospective study done as quality improvement initiative to determine safety and efficacy of Hartman's as a predominant resuscitation fluid shows that it can safely replace HAS and is cost-effective. Therer was a trend towards prolonged PICU stay with use of HAS, however it was not statistically significant. There was no significant difference in delayed chest closure and incidence of AKI between the two cohorts. The main limitaions are: Limitations inherent to retrospective methodology Quality of data/documentation No specific parameters/outcome for resuscitation fluid use Potential variation in practice over time. Recommendations: Hartman's can be safely used as a cost effective replacemnt for HAS in postoperative cardiac surgery fluid resuscitation. Adequately powered multi-centre randomised controlled trials are needed Reference: Dingankar AR et al. Albumin 5% versus crystalloids for fluid resuscitation in children after cardiac surgery. PCCM . 2018;19(9):846–53.